Hukum Memperdagangkan Barang Tiruan Di Aplikasi Online Perspektif Imam Syafi’i (Studi Kasus Di Market Place Shopee Malaysia) - Nurhidayah Binti Suhaizan; Tetty Marlina Tarigan (ARBITER: Jurnal Ilmiah Magister Hukum, 2023)
The main problem in this research is how to review the law of trading counterfeit goods online. The type of research used in this research is a type of literature research (library research), thereby using a qualitative research method with a normative research approach. The results of the research show that: 1) According to Imam Syafi'i, the law of trading counterfeit goods on the Shopee marketplace is not allowed due to the presence of elements that are prohibited or forbidden. The existence of fraudulent elements planned by the seller to deceive the customer is prohibited. This is because there is an element of tadlis in the practice. The element of tadlis which is a fraud committed in a sale and purchase transaction by the seller against the goods/objects he sells to the buyer, it can cause losses for the party who owns registered trademark rights or the owner of original trademark rights that are imitated. 2) How the practice of trading counterfeit goods on the online marketplace Shopee is carried out does not meet the objective requirements of the agreement, which is a certain thing and a halal reason. From the results of this study, the author suggests that the rules on the practice of buying and selling counterfeit goods be strengthened. Because, it can lead to the habit of the community to always use counterfeit goods.